A Methodological Approach for Assessing the Interaction Between Rural Landscapes and Built Structures: A Case Study of Winery Architecture in Tuscany, Italy - Stefano Bigiotti; Carlo Costantino; Mariangela Ludovica Santarsiero; Alvaro Marucci (Land)
This research aims to investigate the dynamics of interaction and interdependence between winery architecture and the rural landscape, with a particular focus on the Tuscany region in Italy. The primary objective is to analyze a selection of wineries deemed iconic and exemplary for the topic, assessing their relationship with the surrounding territory and landscape. To this end, specifically designed analytical frameworks are employed, grounded in experimental methodologies and criteria well-established in the relevant scientific literature. This methodology integrates a wide range of qualitative and quantitative indicators from scientific literature, organizing them within various taxonomic frameworks. Through tailored analytical forms, the research examines how design choices impact the agrarian context, highlighting the pivotal role of winery architecture in strengthening territorial identity and fostering a model of sustainable tourism. This paper introduces an adaptable interpretive method applicable across contexts, suitable for professionals and decision-makers. The findings present a framework for evaluating landscape systems, demonstrating how passive and advanced strategies enhance eco-efficiency and landscape perception, and adding ethical, aesthetic, and functional value. Moreover, the research contributes to rural landscape discourse, highlighting winery architecture’s role in balancing sustainability, driving economic development, and preserving rural environments.